Examining the UK Covid‐19 mortality paradox: Pandemic preparedness, healthcare expenditure, and the nursing workforce. (10th October 2020) - Stribling, Julian; Clifton, Andrew; McGill, George; de Vries, Kay
Abstract: Aim: To examine the UK pandemic preparedness in light of health expenditure, nursing workforce, and mortality rates in and relation to nursing leadership. Background: The Global Health Security Index categorized the preparedness of 195 countries to face a biological threat on a variety of measures, producing an overall score. The United States of America and the United Kingdom were ranked 1st and 2nd most prepared in 2019. Method: A cross‐nation comparison of the top 36 countries ranked by Global Health Security Index score using a variety of online sources, including key data about each nation's expenditure on health and the nursing workforce, and compared these with mortality data for COVID‐19. Results: The extent of a country's pandemic preparedness, expenditure on healthcare and magnitude of the nursing workforce does not appear to impact mortality rates at this stage of the pandemic which is something of a paradox. Conclusion: It is important that arrangements for dealing with future global pandemics involve a range of agencies and experts in the field, including nurse leaders. Implications for Nursing: To achieve the best outcomes for patients, nurse leaders should be involved in policy forums at all levels of government to ensure nurses can influence health policy.